Space in narrative inquiry on second language learning. (November 2021) - Benson, Phil
Abstract: One of the main strengths of narrative inquiry is its capacity to capture change and development over time. At first sight, narrative methods are less suited to investigation of the spatial dimensions of second language learning. This paper outlines the main reasons why narrative research should pay more attention to issues of space. It then outlines what I call a 'spatially aware' approach to narrative research that aims to overcome the tendency to foreground time over space. This approach involves the use of a mobile GPS-enabled diary app and follow-up stimulated recall interviews, that aims to construct spatially-rich narratives of students' language use and learning. Lastly, the paper considers some alternative approaches to incorporating space into narrative research.